The association between isolated oligohydramnios at term and pregnancy outcome and perinatal outcome in case of isolated oligohydramnosis: a retrospective analysis - Kansara, Vijay M.; Kadakar, Kunal D.; Chikani, Akash S.; Pateliya, Pinal A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Current study was carried out to assess the impact of isolated oligohydramnios on perinatal outcomes and mode of delivery. Methods: A retrospective observational cohort study was conducted at term pregnancy with sonographic finding of isolated oligohydramnios (AFI <5 cm) were recruited for the study. Uterine anomaly and high risk pregnancies were excluded from the study. The mode of delivery and perinatal outcome were compared with control group of pregnancy with normal amniotic fluid (AFI >5-25 cm). Results: When compared to the normal AFI, women with oligohydramnios had significantly lower birth weight babies and were delivered at a significantly earlier gestational age. However there was no difference in the APGAR scores at birth and NICU admissions between the two groups. Reactive NST had more chances of good APGAR score at 1 and 5 minute and that lower the AFI more the probability of nonreactive NST and abnormal Doppler. The number of inductions and caesareans done for foetal reasons were significantly higher in the exposed group. Conclusions: Obstetric and perinatal outcome remains similar in both isolated oligohydramnios with reactive NST as well as in patients with normal amniotic fluid index. Isolated oligohydramnios is not associated with adverse perinatal outcomes. However, it increases the risk for labour induction and caesarean section.